2019
DOI: 10.1007/s12053-019-09822-x
|View full text |Cite
|
Sign up to set email alerts
|

Inter-organizational collaboration for energy efficiency in the maritime sector: the case of a database project

Abstract: This article explores the complexities of establishing knowledge-sharing practices between organizations through a case study of the creation of a database for energy efficiency measures relevant to the shipping sector. As researchers and policy-makers tend to point towards knowledge sharing and collaboration as means towards a more energy-efficient society, there is a need to better understand the knowledge sharing practices in such initiatives. The study is based upon extensive fieldwork where the first auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Being part of an industrial network is a wellestablished measure found to be successful in earlier studies (e.g. Backman, 2018;Borg & von Knorring, 2019;Köwener et al, 2011;Palm & Backman, 2017) and that seems to be applicable in this case as well. Several interviewees mentioned network collaborations as import for diffusing knowledge and information.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Being part of an industrial network is a wellestablished measure found to be successful in earlier studies (e.g. Backman, 2018;Borg & von Knorring, 2019;Köwener et al, 2011;Palm & Backman, 2017) and that seems to be applicable in this case as well. Several interviewees mentioned network collaborations as import for diffusing knowledge and information.…”
Section: Discussionmentioning
confidence: 85%
“…Networking and increased dialogue through actor networks in the sector can however be a driver of improved energy efficiency in the sector if used to clarify, analyse and communicate, for example requirements. Information hubs and the existence of industrial networks for sharing experience and raising awareness of energy-efficiency measures have proven successful in increasing companies' interest and engagement in energy issues (Butturi et al, 2019;Durand et al, 2018;Palm & Backman, 2017;Peel et al, 2020;Solnørdal & Foss, 2018). Dialogues and networking also benefit creative processes and innovation (Lazoroska & Palm, 2019;Palm & Backman, 2017;Westerlund et al, 2014).…”
Section: Identified Barriers and Drivers To Energy Efficiencymentioning
confidence: 99%
“…They require development and testing of novel concepts on a global scale, large investments in technologies, and infrastructures with little immediate benefits and complex coordination between regulatory and private bodies. Even the most rational, cost-effective measures may be overlooked if they do not fit into existing work practices, competences, or institutions (Shove 1998;Viktorelius 2020;von Knorring 2019).…”
Section: Introductionmentioning
confidence: 99%